PERANCANGAN PROYEK HOTEL DENGAN PENDALAMAN SENSE OF PLACE OLEH KONSULTAN ARSITEKTUR INTERIOR NOOK STUDIO - Adeline Nadya Kwandy; Dyah Kusuma Wardhani (KREASI, 2023)
Final Assignment Report titled Hotel Project Design with In-Depth Sense of Place by Interior Architecture ConsultantNook Studio contains the design plans for a hotel project located in Canggu, Bali, precisely on Bumbak Dauh Street number 20, Kerobokan, North Kuta, Badung Regency, Bali 80361. The Oasis hotel design concept refers to the local community’s philosophy of life, namely Tri Hita Karana which is implemented in harmony with nature and the environment. One way to achieve the intended balance is to design using materials with a strong natural feel. The use of natural elements includes wood, natural stones, and greenery. The primary objective of this project is to create a sense of place by incorporating Balinese locale throughout the hotel design. The concept applied in this design project is also based on local cultural and local values and is modernized and adapted to current developments. To create a cohesive design that harmoniously blends the past. The research method used in this research process is qualitative by observing the physical elements of the potential site. It is hoped that the results of this research will be a descriptive sense of place through the application of physical and social elements in the hotel project design and can provide attachment and impression for visitors so that visitors want to come back.